Le indagini internazionali OCSE e IEA del 2015 Contributi di approfondimento - Palmerio, Laura; Caponera, Elisa (INVALSI per la ricerca - Open Access, 2019)
The volume aims to promote the scientific value of the data collected by the international OECD and IEA surveys carried out in 2015. In particular, as regards the IEA TIMSS and TIMSS Advanced surveys, the contributions focus on the incidence of behaviours and learning contexts of students on the development of skills in mathematics. Regarding the OECD PISA survey, the topics discussed are the relationship between cultural, cognitive and motivational factors and the relative empirical evidence, as well as the online media exposure of the survey. Finally, a last thematic section concerns the relationship between context variables and competences related to Financial Literacy.